The Resurgence of Nationalism in the European Union - Madalina Calance (CES Working Papers, 2012)
Considering the process of integration and the enlargement of the European Union, the continent's political map changed significantly during the last decades. For most of the European nations, facing the integration is going on the path of the economic and social improvement, which also involves important aspects about the nation-state (national identity, nationalism). This paper will focus on the meanings and the dimensions of contemporary nationalism and will later look at the impact of the nationalist ideas in the EU, in times of recession. The study found out that there are many perspectives of the EU challenging national economies and the state sovereignty but, at the same time, people are aware the imminence of the European identity in their economic and cultural future.
Keywords: F15; F52; F59; 330; nationalism; national identity; European identity; immigration; populist parties Romania